2009
DOI: 10.1007/s00404-009-1306-7
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in age-related changes of postpartum hemoglobin levels

Abstract: These results suggest an ethnic difference in the age trends of postpartum Hb levels. Clinically, significant changes may occur between the ages of 27 and 30 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This suggests that the clusters obtained with age-corrected marker values are more biologically uniform for diabetic patients and less uniform for the general population. These inconsistencies can be explained, at least in part, by complex and non-linear interactions between age and marker levels [15], [16], which can interfere with the relatively simple linear correction method we have used in this study. In fact, we have shown that age effects are more linear in advanced ages (>50), making linear age correction more appropriate in generally older diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the clusters obtained with age-corrected marker values are more biologically uniform for diabetic patients and less uniform for the general population. These inconsistencies can be explained, at least in part, by complex and non-linear interactions between age and marker levels [15], [16], which can interfere with the relatively simple linear correction method we have used in this study. In fact, we have shown that age effects are more linear in advanced ages (>50), making linear age correction more appropriate in generally older diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the knowledge-base contains patterns extracted from raw clinical data. Earlier analysis of such patterns, using data sources such as the National Health and Environmental Nutrition Survey and the Soroka Maternity Database showed that non-trivial age trends can be extracted from raw clinical data [ 8 , 9 ]. By combining these patterns with the age-related knowledge to be found in the research corpus, it should be possible to suggest new ways to consider patient age in the improvement of patient care and to propose new research avenues.…”
Section: Introductionmentioning
confidence: 99%